Study the effect of screw speed and temperature profile on structure, thermal and physical properties of melt blended polyamide 6/MMT nanocomposites - Zulhelmi, Ismail (2013)
In this thesis, the effect of screw speed and temperature profile during the extrusion of polyamide 6/montmorillonite nanocomposites was discussed. The clay content (1 to 5 of weight percentage), screw speed (100 rpm to 300 rpm) and temperature barrel profile of co rotating twin-screw extruder were varied. Polyamide 6 (PA6) and montmorillonite (MMT) were melt blended under on/off and automatic heating of extrusion for a comparative study. The morphology of PA6/MMT nanocomposite was determined through the application of x-ray diffraction (XRD) and field emission scanning electron microscope (FESEM), while the thermal properties of the sample were analyzed from the thermogravimetric analysis (TGA). The differential scanning calorimetry (DSC) is used to determine the physical characteristic of PA6/MMT nanocomposite. Optimal dispersion of MMT occurred at low content of clay. Exfoliated structure was consistently obtained for PA6-1, while the collapse of d-spacing was mainly observed for PA6-3 and PA6-5. The presence of agglomerated MMT for PA6-5 proved the tendency of MMT in agglomeration at higher MMT content. The thermal stability of PA6/MMT nanocomposite was improved only at 1 wt. % of MMT and incorporation of more MMT reduced it further. The on/off heating method increased the thermal stability of PA6-1, while the effect was varied for PA6-3 and PA6-5. The on/off heating extruded PA6-1 possessed lower value of crystallinity but melting and crystallization temperature was measured at similar value as automatic heating extruded PA6-1.